STUDI ANALISIS PENERAPAN MANAJEMEN KELEMBAGAAN SMA SYUBBANUL WATHON SECANG MAGELANG - Rozaq, Mohammad Khoirur; Ni’mah, Khoirotun; Fadila, Nisya’ Aulia; Wulandari, Eka (STAI Pelabuhan Ratu, 2024)
This research aims to analyze KH. Hasyim Asy'ari's views on women's education, explore the foundations of his thoughts on the importance of equality in education, and identify the implications of these views for social and cultural development. Using a qualitative approach with a literature study method, data were collected through an analysis of literature that includes the works of KH. Hasyim Asy'ari, articles, books, and other relevant sources. The results of the research show that KH. Hasyim Asy'ari had a progressive view on women's education, emphasizing equality and the importance of access to education for all genders. He believed that women's education is a fundamental and essential right to improve the quality of individuals, families, and society. KH. Hasyim Asy'ari saw women as the primary educators of future generations, so their education would have a positive impact on social and cultural development. He rejected the view that limits women's roles to the domestic sphere without access to education and emphasized that Islam strongly encourages women to seek knowledge. Thus, women's education according to KH. Hasyim Asy'ari is considered the key to the advancement of civilization. These findings indicate that KH. Hasyim Asy'ari's teachings are relevant and can be applied in efforts to improve the quality of women's education in the modern era.